2019
DOI: 10.1186/s12916-019-1268-y
|View full text |Cite
|
Sign up to set email alerts
|

Cathelicidin-related antimicrobial peptide protects against myocardial ischemia/reperfusion injury

Abstract: Background Cathelicidins are a major group of natural antimicrobial peptides which play essential roles in regulating host defense and immunity. In addition to the antimicrobial and immunomodulatory activities, recent studies have reported the involvement of cathelicidins in cardiovascular diseases by regulating inflammatory response and microvascular dysfunction. However, the role of cathelicidins in myocardial apoptosis upon cardiac ischemia/reperfusion (I/R) injury remains largely unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 64 publications
3
63
0
Order By: Relevance
“…In addition, ours and other studies have shown that CRAMP directly attenuates stimuli‐triggered inflammatory responses in various cell types by directly interacting with bacterial endotoxin, activating pattern recognition receptors, or affecting intracellular inflammatory signalling (Hilchie et al, ; Mookherjee et al, ; Sun et al, ). Further, we also demonstrated that CRAMP could prevent cellular apoptosis by modulating apoptotic pathways and associated proteins (Bei et al, ; Sun et al, ).…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…In addition, ours and other studies have shown that CRAMP directly attenuates stimuli‐triggered inflammatory responses in various cell types by directly interacting with bacterial endotoxin, activating pattern recognition receptors, or affecting intracellular inflammatory signalling (Hilchie et al, ; Mookherjee et al, ; Sun et al, ). Further, we also demonstrated that CRAMP could prevent cellular apoptosis by modulating apoptotic pathways and associated proteins (Bei et al, ; Sun et al, ).…”
Section: Introductionmentioning
confidence: 55%
“…Our recent work has demonstrated that peripheral non‐immune cells are a source of CRAMP with cytoprotective and immunomodulatory actions (Bei et al, ; Sun, Furio, et al, ; Sun et al, ). In this study, we extended our investigations to analyse the effects of CRAMP on renal I/R injury and the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Myocardial cell apoptosis mainly occurs in the surviving portion of the heart which contributes to the loss of myocardial cells and inhibits left ventricular remodelling after MI/R injury, and the increase in myocardial cell apoptosis is positively correlated with the occurrence of cardiac failure after MI/R injury. 7,8 Therefore, inhibiting myocardial cell apoptosis is important for the prevention and treatment of MI/R injury. 7,8 Therefore, inhibiting myocardial cell apoptosis is important for the prevention and treatment of MI/R injury.…”
mentioning
confidence: 99%
“…6 So, apoptosis of myocardial cells is a key promoting factor contributing to cardiac failure after MI/R injury. 7,8 Therefore, inhibiting myocardial cell apoptosis is important for the prevention and treatment of MI/R injury.…”
mentioning
confidence: 99%